Transcendent Philosophy: A Comparative Study on Mulla Sadra and Kant - Fatemeh Sadat Basirizadeh; Narges Raoufzadeh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
In this paper, the author attempts to talk about the truth and objectivity of propositions in practical philosophy through a comparative method and the investigation of the philosophical principles of Kant and Mulla Sadra so as to feature the significance of the standards of the Transcendent Philosophy and investigates the view of both philosophers. It is also an investigation of Kant's refusal of presence as a genuine predicate, from one perspective, and Mulla Sadra's affirmation and exhibition of such predicates, on the other.